(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay remembers Guido Davide Neri in his distinctive feature of indecisive philosopher. Neri’s indecision takes root in his relationship with history, inducing him to interpret the running of time as it would be never closed by a clear decision that, as the latin word explains, would imply a cut and a loss of each historical event’s meaning.